Event-free survival by residual cancer burden with pembrolizumab in early-stage TNBC: exploratory analysis from KEYNOTE-522 - Pusztai, L.; Denkert, C.; O'Shaughnessy, J.; Cortes, J.; Dent, R.; McArthur, H.; Kümmel, S.; Bergh, J.; Park, Y. H.; Hui, R.; Harbeck, N.; Takahashi, M.; et al. (Annals of Oncology, 2024)
Background: KEYNOTE-522 demonstrated statistically significant improvements in pathological complete response (pCR) with neoadjuvant pembrolizumab plus chemotherapy and event-free survival (EFS) with neoadjuvant pembrolizumab plus chemotherapy followed by adjuvant pembrolizumab in patients with high-risk, early-stage triple-negative breast cancer (TNBC). Prior studies have shown the prognostic value of the residual cancer burden (RCB) index to quantify the extent of residual disease after neoadjuvant chemotherapy. In this preplanned exploratory analysis, we assessed RCB distribution and EFS within RCB categories by treatment group. Patients and methods: A total of 1174 patients with stage T1c/N1-2 or T2-4/N0-2 TNBC were randomized 2 : 1 to pembrolizumab 200 mg or placebo every 3 weeks given with four cycles of paclitaxel + carboplatin, followed by four cycles of doxorubicin or epirubicin + cyclophosphamide. After surgery, patients received pembrolizumab or placebo for nine cycles or until recurrence or unacceptable toxicity. Primary endpoints are pCR and EFS. RCB is a prespecified exploratory endpoint. The association between EFS and RCB was assessed using a Cox regression model. Results: Pembrolizumab shifted patients into lower RCB categories across the entire spectrum compared with placebo. There were more patients in the pembrolizumab group with RCB-0 (pCR), and fewer patients in the pembrolizumab group with RCB-1, RCB-2, and RCB-3. The corresponding hazard ratios (95% confidence intervals) for EFS were 0.70 (0.38-1.31), 0.92 (0.39-2.20), 0.52 (0.32-0.82), and 1.24 (0.69-2.23). The most common first EFS events were distant recurrences, with fewer in the pembrolizumab group across all RCB categories. Among patients with RCB-0/1, more than half [21/38 (55.3%)] of all events were central nervous system recurrences, with 13/22 (59.1%) in the pembrolizumab group and 8/16 (50.0%) in the placebo group. Conclusions: Addition of pembrolizumab to chemotherapy resulted in fewer EFS events in the RCB-0, RCB-1, and RCB-2 categories, with the greatest benefit in RCB-2. These findings demonstrate that pembrolizumab not only increased pCR rates, but also improved EFS among most patients who do not have a pCR.
CRIS-Team Scopus Importer:2024-04-12
Keywords: chemotherapy; event-free survival; immunotherapy; pembrolizumab; residual cancer burden; triple-negative breast cancer